Pelatihan Desain Grafis Untuk Para Siswi MA Muqimus Sunnah Palembang - Pratama, Dicky; Alamsyah, Derry; Gasim, Gasim; Elizabeth, Triana; Yoannita, Yoannita; Tinaliah, Tinaliah (FORDICATE, 2021)
Community service activity in the form of providing training wereheld on Friday, July 5, 2019 at the MA Muqimus Sunnah School inPalembang. This training aims to conduct graphic design training usingAdobe Photoshop application for 25 students to improve their knowledge inpractice about how to create two dimensional design using Adobe Photoshopapplication such as logo design, poster design, and photo editing. This activityinclude substantial information of the activity, followed by demonstrations inpracticing the application to create designs and testing activities to know howmuch the students can understand the training materials that have beenprovided. At practical session on designing logo and poster, participants weregiven guidance on concepts of how to make good logo such as in choosingcolors, shapes, sizes, and letters or numbers used on logo, The results of thetraining show the students can understand and use tools in Adobe Photoshopapplication to add and organize text, cut and move images, students cancreate logos, posters, and edit images/photos using Adobe Photoshopapplications.